Synthesis of MeOH and DME From CO2 Hydrogenation Over Commercial and Modified Catalysts - Santiago, Rafaelle G.; Coelho, Juliana A.; Lucena, Sebastião M. P. de; Musse, Ana Paula S.; Portilho, Marcio de F.; Rodriguez-Castellón, Enrique; Azevedo, Diana C. S. de; Bastos-Neto, Moises (Frontiers in Chemistry, 2022)
Growing concern about climate change has been driving the search of solutions to mitigate greenhouse-gas emissions. In this context, carbon capture and utilization (CCU) technologies have been proposed and developed as means of giving CO2 a sustainable and economically viable destination. An interesting approach is the conversion of CO2 into valuable chemicals, such as methanol (MeOH) and dimethyl ether (DME) through the catalytic hydrogenation of CO2 on Cu, Zn and Al based catalysts. In this work, three catalysts for the MeOH and DME synthesis from CO2 were tested using a single fixed bed reactor. The first was a commercial CuO/-Al2O3, the second CuO-ZnO/-Al2O3, obtained via incipient wetness impregnation of the first catalyst with an aqueous solution of zinc acetate, and the third was a CZA catalyst obtained by the coprecipitation method. The samples were characterized by XRD, XRF and N2 adsorption isotherms. The hydrogenation of CO2 was performed at 25 bar, 230 °C, with a H2:CO2 stoichiometric ratio of 3 and space velocity of 1200 mL (g cat · h)-1 in order to assess the potential of these catalysts in the conversion of CO2 in methanol and dimethyl ether. The catalysts activity was correlated to the adsorption isotherms of each reactant. The main results show that the highest CO2 conversion and the best yield of methanol are obtained with the CZACP catalyst supposedly due to its higher adsorption capacity of H2. In addition, although the presence of zinc oxide reduces the textural properties, the CZAWI catalyst showed higher CO2 conversion than commercial material CA.